Functional Analytic Psychotherapy in Germany: Uses and acceptability reported by therapists (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Functional Analytic Psychotherapy (FAP) is a behavioral analytic strategy for psychotherapy which has been expanding through several countries throughout the decades. However, in some European countries, particularly in Germany, FAP is still incipient. The aim of the study was to identify therapies used by German psychologists, and to investigate the usages and acceptance of FAP-type techniques. To achieve this, 1,586 German behavior therapists were invited to participate in the study. Fifty therapists answered the survey, which contained ten questions in a four-point Likert scale and two multiple choice questions. A descriptive and exploratory analysis and multivariate statistic technique was conducted. Results indicated that most of them make use of procedures in a clinical context which are similar to the therapeutic techniques of FAP and evaluate them as therapeutic.
Keywords: functional analytic psychotherapy; psychology in Germany; contextual therapies; behavior therapy; transculturality.